Burn Care in Kirtipur Hospital before and during COVID 19 Pandemic: Survey of Psychological Issues and Practice Behaviours of Burn Care Personnel - Nakarmi, KK; Basnet, SJ; Karki, B; Ghartimagar, M; Nagarkoti, KK; Yadav, MK; Rai, SM (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Introduction: The COVID 19 pandemic has adversely impacted all aspects of health care throughout the world. Burn care in lower and middle income countries has suffered the most. We aimed to compare burn care at Kirtipur Hospital before and during the pandemic and explore psychological issues and practice behaviour among burn care worker (BCW). Methods: Retrospective data analysis of burn patients admitted during April to August of 2019 and 2020 was done. Internet based survey of BCW was done. Results: Burn admissions, demographics and characteristics did not change. Fewer surgeries were undertaken in 2020. Almost half of the BCW worked 12 hours shift or longer. Most were working on half pay. Nearly everyone was using hand sanitizers, hand washing and masks. Few had access to level II personal protective equipments (PPE) to see suspected patients; fewer had access to face shield, KN 95 masks and boot. Even gloves and caps were scarce. Many feared getting themselves or family members infected. Majority realized the need of clear hospital policy on how they would be managed when infected. Conclusion: Number, types, severity and mortality did not change. Number of surgeries decreased. Issues like pay cuts, longer working hours and lack of PPEs were reported by majority. J Bangladesh Coll Phys Surg 2021; 39: 241-248